2007
DOI: 10.1016/j.ygeno.2007.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional response of porcine mesenteric lymph nodes to Salmonella enterica serovar Typhimurium

Abstract: To elucidate the host transcriptional response to Salmonella enterica serovar Typhimurium, Affymetrix porcine GeneChip analysis of pig mesenteric lymph nodes was used to identify 848 genes showing differential expression across different times after inoculation or when compared to non-inoculated controls. Annotation analyses showed that a high proportion of these differentially expressed (DE) genes are involved in immune and inflammatory responses. T helper 1, innate/inflammatory, and antigen-processing pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…However, its cytokine activity relies on its cleavage for extracellular proteases such as elastase [23], whose activity could be reduced due to up-regulation of serpins, as it has been described above. An increased expression of the gene coding for this protein has been previously reported after S. Typhimurium infection in porcine mesenteric lymph nodes [24]. Finally, it is interesting to note the down-regulation of FAM49B, a protein whose function is not yet well established, but interacts with human IκB kinase epsilon [25], is a key regulator of NFκB activity [26], and could be implicated in the inflammatory response upon Salmonella infection.…”
Section: Immunoregulatory Proteins: Inflammation and Innate Immune Rementioning
confidence: 66%
“…However, its cytokine activity relies on its cleavage for extracellular proteases such as elastase [23], whose activity could be reduced due to up-regulation of serpins, as it has been described above. An increased expression of the gene coding for this protein has been previously reported after S. Typhimurium infection in porcine mesenteric lymph nodes [24]. Finally, it is interesting to note the down-regulation of FAM49B, a protein whose function is not yet well established, but interacts with human IκB kinase epsilon [25], is a key regulator of NFκB activity [26], and could be implicated in the inflammatory response upon Salmonella infection.…”
Section: Immunoregulatory Proteins: Inflammation and Innate Immune Rementioning
confidence: 66%
“…The current Affymetrix Porcine GeneChip is a complete, pangenomic array and has been used mainly for global transcriptional profiling of the pig genome, as it is the most sensitive and reproducible for swine genomic studies (Tsai et al, 2006). However, it has also been used to observe the transcriptional changes of 848 genes of pig mesenteric lymph nodes in response to Salmonella typhimurium infection (Wang et al, 2007), and Genini et al (2008) reported the expression alteration of 1409 genes of primary porcine alveolar macrophages following infection with porcine reproductive and respiratory syndrome virus. The present study provides the first pangenomic microarray analysis of pig transcriptional responses to CSFV infection, in which the genomic transcriptional levels of porcine peripheral blood leukocytes (PBLs) prepared from CSFV-inoculated pigs with severe clinical symptoms were analysed by using the Affymetrix Porcine GeneChip, showing that 1745 genes were up-or downregulated by at least 2-fold following infection.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, it is considered a marker for many types of inflammatory disease including arthritis, asthma, cystic fibrosis and chronic inflammatory bowel diseases [3,4,5,6]. In pigs, the S100A12 gene is highly expressed in immune-related tissues and is up-regulated during infections with HPS, Salmonella , or PCV2 [17,19,21]. Expression of the S100A12 gene was up-regulated after stimulation with LPS or Poly I: C indicating that S100A12 is likely also important in the inflammatory response in pigs [19].…”
Section: Resultsmentioning
confidence: 99%